Influence of Welding Parameters on the Tensile Properties of ASTM A36 Using FCAW for Medical Storage Applications - Moh. Dimas Hakim; Eli Novita Sari; Dian Ridlo Pamuji; I.G.N.B. Catrawedarma; Mohammad Abdul Wahid; Akhmad Afandi (Global Scientific Media, 2025)
This study investigates the influence of welding parameters on the tensile properties of ASTM A36 steel using the Flux Cored Arc Welding (FCAW) method for medical storage applications. ASTM A36 is widely used due to its good weldability and ductility, making it suitable for tank fabrication in medical systems. The research focuses on the effects of varying current (120 A, 135 A, 150 A) and voltage (22 V, 24 V) settings without the application of Post Weld Heat Treatment (PWHT). Tensile tests were performed to assess the mechanical strength of the welded joints. The results indicate that the welding setting of 120 A and 22 V produced the highest tensile strength of 464.8 MPa. In contrast, higher current settings, particularly 135 A, led to a reduction in tensile performance. The findings demonstrate that appropriate control of welding parameters is crucial to achieving optimal tensile strength in FCAW-welded ASTM A36 components for medical storage systems.